VERTICAL ZONING AS A METHOD OF ENVIRONMENTAL CONSERVATION HISTORIC CITY - and (Municipal economy of cities. Series: «Economy science», 2013)
The question of integrated development of underground space in the historic centers of the largest cities in Ukraine to resolve territorial , transportation and environmental issues. <span title="Визначено основні напрями сучасного використання підземного простору (перелічено, які з них застосовуються в Україні і зокрема в Харкові), наведено пропозиції використання підземного простору в центральній частині міста при розробці">The main trends of the modern use of underground space ( lists , which are used in Ukraine in Kharkiv in particular ) are offers use of underground space in the central part of the development measures for the implementation of the master plan.